Aplikasi Rekayasa Nilai (Value Engineering) Pada Desain Tungku Briket Arang Biomassa Sistem Kontinyu Berpengapian Semi Otomatis Sebagai Upaya Mempermudah Pemanfaatan Energi Alternatif Mengganti Minyak Tanah - Wijana, Made; Joniarta, I Wayan (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2012)
The biomassa charcoal briquet is one of principal component of cooking in household scale which has some weakness in its operation, such as take a long time for beginning ignitation, flame energy is not stable, the putting out can not be done quickly, once filling up for once cooking. Impractical operational of briquet stove  caused people did not want to change the use of petroleum stove to the use  of biomass briquet stove. Hence, biomass charcoal briquet stove is modified in order to simplify its operation by increase fungsional aspect, technique aspect, and economical aspect.            The method used in this research is value engineering method in order to choose one alternative of modification of biomass charcoal briquet  stove and analyze with five phase of job planning that include (1) information phase, (2) creative phase, (3) analysis phase, (4) development phase, and (5) presentation phase.            At the analysis phase, it is made analysis to eight alternatives of modification and one initial design which is used as reference of performance evaluation. The evaluation result at development phase is the seventh alternative of modification has the highest value that is 1,358 with performance 425,10 and gives some advantages, those are cooking speed is increased (boilling water in seven minute per liter), operational simplicity is very increased that is once filling up for cooking repeatedly (continue system), cutting out of fire can be done quickly without taking apart of stove (semi automatic), pollution is decreased and stinging smell is not happen.            Biomass charcoal briquet stove has high economic value, because its operasional is almost the same as petroleum stove and its operational cost is a quarter of petroleum stove cost.  So, it is good to be developed and applied to society.